Electricity production potential and social benefits from rice husk, a case study in Pakistan. Issue 1 (31st December 2016) - Mohiuddin, Obaidullah; Mohiuddin, Abdullah; Obaidullah, Madina; Ahmed, Humayun; Asumadu-Sarkodie, Samuel
Abstract: Pakistan has been experiencing energy crisis owing to its sole dependence on fossil fuels. Reduction in local fossil fuel reserves has led to an increase in their prices, thereby increasing the cost of electricity. Since the tariff remains the same, Pakistan is over-burdened with circular debts and observes a daily power shortfall of about 12–14 h. Being an Agra-economic country, many major and minor crops are produced and exported in large quantities. This results in a bulk of the agricultural waste which are not utilized. The waste can be utilized to meet the country's energy demand while mitigating climate change and its impact. The study examines the electricity production potential and social benefits of rice husk in Pakistan. It is estimated in this study that if 70% of rice husk residues are utilized, there will be annual electricity production of 1, 328 GWh and the cost of per unit electricity by rice husk is found at 47.36 cents/kWh as compared to 55.22 cents/kWh of electricity generated by coal. Importantly, the study will increase the awareness of the benefits of utilizing agricultural waste for useful products such as silica, with several social and environmental benefits such as a reduction of 36, 042 tCO2e /yr of methane, reducing carbon dioxide emissions, improving the air quality, and providing 4.5 k new jobs. The paper concludes with the policy recommendations based on this study.